2020
DOI: 10.29309/tpmj/2020.27.06.3549
|View full text |Cite
|
Sign up to set email alerts
|

Clipless laparoscopic cholecystectomy: 3 Port access.

Abstract: Objectives: Use to ultrasound vibrations instead of electric current makes Harmonic Scalpel a safer and more efficient instrument for dissection during laparoscopic surgeries. The property of both coagulation and cutting using single Harmonic Scalpel instruments saves time of surgery reducing anesthesia load. Cystic artery and liver bed dissection has been widely used and established but a contemporary approach is the coagulation and cutting of cystic duct with Harmonic Scalpel eliminating the need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…9 similarly, inconsistent results were reported by another study conducted in Rawalpindi in which it was seen that the frequency of gall bladder perforation was same in both groups (2 [3.4%] vs. 2 [3.6] respectively with P-value=0.972). 8 These variations in the literature makes the evidence based use of harmonic scalpel a controversy during laproscopic surgery. A study by Roberta Gelmini et al presented that the mean operative time was significantly shorter in patients treated with the Harmonic scalpel.…”
Section: Discussionmentioning
confidence: 99%
“…9 similarly, inconsistent results were reported by another study conducted in Rawalpindi in which it was seen that the frequency of gall bladder perforation was same in both groups (2 [3.4%] vs. 2 [3.6] respectively with P-value=0.972). 8 These variations in the literature makes the evidence based use of harmonic scalpel a controversy during laproscopic surgery. A study by Roberta Gelmini et al presented that the mean operative time was significantly shorter in patients treated with the Harmonic scalpel.…”
Section: Discussionmentioning
confidence: 99%
“…9 similarly, inconsistent results were reported by another study conducted in Rawalpindi in which it was seen that the frequency of gall bladder perforation was same in both groups (2 [3.4%] vs. 2 [3.6] respectively with P-value=0.972). 8 These variations in the literature makes the evidence based use of harmonic scalpel a controversy during laproscopic surgery. A study by Roberta Gelmini et al presented that the mean operative time was significantly shorter in patients treated with the Harmonic scalpel.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, another study conducted in Rawalpindi also reported same frequency of biliary leakage in both groups (2 [3.4%] vs. 2 [3.6] respectively with P-value=0.972). 8 the results of the study conducted by Hassan et al also endorsed these findings by reporting the rate of biliary as 1.7% with clipless method and 3.3% with clipped method which was not statistically significant (p = 0.45). 9 The aim of this study was to compare the frequency of biliary leakage with clipless versus clipped Laparoscopic Cholecystectomy for management of Cholecystitis.…”
Section: Introductionmentioning
confidence: 87%
“…All these prolong the hospital stay of the patient, thus increasing the financial burden on the patient, his family and the health facility and most of all increase the morbidity and mortality. 3 Harmonic scalpel is an option for the clipless surgery and has been considered as a better choice for securing the cystic artery and cystic duct in order to prevent the risk of biliary leakage following clipped laparoscopic cholecystectomy. 4,5 Multiple studies have reported that the incidence of biliary leakage was more in clipped as compared to clipless surgeries, respectively.…”
Section: Original Articlementioning
confidence: 99%
“…8 Others have also observed that the clipped procedures resulted in higher incidence of biliary leakage. 3,9 The purpose of this study was to compare the efficacy of clipped and clipless cholecystectomy in the management of gallstone-related cholecystitis. Local data regarding newer techniques is very limited.…”
Section: Original Articlementioning
confidence: 99%